2020
DOI: 10.1007/s10072-020-04321-9
|View full text |Cite
|
Sign up to set email alerts
|

Using NMR spectroscopy to investigate the role played by copper in prion diseases

Abstract: Prion diseases are a group of rare neurodegenerative disorders that develop as a result of the conformational conversion of normal prion protein (PrP C) to the disease-associated isoform (PrP Sc). The mechanism that actually causes disease remains unclear. However, the mechanism underlying the conformational transformation of prion protein is partially understood-in particular, there is strong evidence that copper ions play a significant functional role in prion proteins and in their conformational conversion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 285 publications
(374 reference statements)
0
6
0
Order By: Relevance
“…It has been shown that this aggregation process is triggered by binding between PrP and Cu 2+ ( 44 ). Because Cu 2+ binds to the N-terminal region in histidine residues, Cu 2+ affects its flexibility and initiates conformational changes ( 45 , 46 ). Therefore, our result that rPrP was unable to undergo LLPS in the presence of Cu 2+ can be explained by the loss of flexibility of the N-terminal region due to Cu 2+ and rPrP binding.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that this aggregation process is triggered by binding between PrP and Cu 2+ ( 44 ). Because Cu 2+ binds to the N-terminal region in histidine residues, Cu 2+ affects its flexibility and initiates conformational changes ( 45 , 46 ). Therefore, our result that rPrP was unable to undergo LLPS in the presence of Cu 2+ can be explained by the loss of flexibility of the N-terminal region due to Cu 2+ and rPrP binding.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of copper (Cu(II), Cu 2+ ) to PrP C facilitates redox balance and copper homeostasis [ 289 ] both of which are often disturbed in the TME where cancer drug resistance is associated with higher serum copper levels in patients compared to healthy controls or patients who responded to chemotherapy [ 290 , 291 ]. Copper also changes the conformation of the N-terminal domain [ 292 , 293 , 294 , 295 ], which may impede LLPS [ 121 , 296 ] or even prevent the formation of straight β-strands backbone structures in the infectious PrP Sc form when bound to the non-octarepeat peptides (residues 92–96) [ 297 , 298 ]. However, the Cu 2+ inhibition of amyloid formation is dependent upon binding capacity that becomes less effective at a lower pH [ 93 , 299 ], which is characteristic of most TMEs.…”
Section: Liquid–liquid Phase Separation May Regulate Prion Conversion...mentioning
confidence: 99%
“…Metal ions may regulate the toxicity related to amyloidal oligomers by modulating the aggregation kinetics and oligomer conformation. Moreover, metals can also direct the aggregation towards more toxic species, and generate reactive oxygen species [ 15 , 80 ].…”
Section: Factors Influencing Aggregationmentioning
confidence: 99%
“…Around approximately 50 peptides and proteins are known to form amyloid fibrils in humans and are associated with diseases [ 5 , 6 , 7 ]. These include α-synuclein (α-Syn) in Parkinson’s disease (PD) [ 8 , 9 , 10 ], amyloid beta (Aβ) and Tau in Alzheimer’s disease (AD) [ 11 , 12 , 13 ], prion protein (PrP) in prion disease [ 14 ], and islet amyloid peptide (IAPP), also known as amylin, in type 2 diabetes mellitus (T2DM) [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%